2006
DOI: 10.1089/ars.2006.8.609
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Damage and Platelet Activation as New Predictors of Mobility Disability and Mortality in Elders

Abstract: Mobility disability is an early phase of the disablement process in older adults, and represents a major risk factor for physical disability and mortality. Pathophysiological mechanisms responsible for the onset of mobility limitation are still largely unknown. Oxidative damage, responsible for the disruption of the equilibrium of biological systems by damaging major constituent molecules, might play an important role in the pathway leading to major health-related events. It has been suggested the existence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 122 publications
2
19
0
Order By: Relevance
“…The close relationship between inflammation and oxidative damage [6, 15, 22, 63] is supported by previous studies from our group demonstrating that virtually all cells from classical target organs of cardiovascular diseases are affected by ROS overproduction [7, 15, 2023, 64, 65], mainly by the NADPH oxidases, which also are the main sources of ROS in phagocytic cells [66]. The present findings support the idea that the deleterious effects of ROS are not restricted to hypercholesterolemia and that they may be enhanced by aging, can occur in classical target tissue (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The close relationship between inflammation and oxidative damage [6, 15, 22, 63] is supported by previous studies from our group demonstrating that virtually all cells from classical target organs of cardiovascular diseases are affected by ROS overproduction [7, 15, 2023, 64, 65], mainly by the NADPH oxidases, which also are the main sources of ROS in phagocytic cells [66]. The present findings support the idea that the deleterious effects of ROS are not restricted to hypercholesterolemia and that they may be enhanced by aging, can occur in classical target tissue (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Isoprostanes represent a family of prostaglandin isomers which, in contrast to classic prostaglandins formed through an enzymatic action of the prostaglandin-H-synthase from arachidonic acid, result from a free radicalcatalyzed mechanism [12]. For this reason, isoprostanes provide an optimal estimate of oxidative damage to cellular lipids [13] and represent an excellent biomarker of lipid peroxidation for aging studies [14].…”
Section: Non-enzymatic Antioxidantsmentioning
confidence: 99%
“…3 Redox imbalance is believed to play a causative role in a plethora of unwanted effects or diseases, as well as premature aging; cardiovascular, hepatic, and neurodegenerative diseases; inflammatory conditions; obesity; cancer susceptibility; and cell death. [2][3][4][5] These effects are exerted differently according to individual variability linked with genetic variants in oxidative stress-related genes, as single-nucleotide polymorphisms in some cytosolic and/or mitochondrial antioxidant enzymes. 6 Regular aerobic exercise is well known to modulate redox condition and ameliorate quality of life, particularly in older people, in which it decreases morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…6 Regular aerobic exercise is well known to modulate redox condition and ameliorate quality of life, particularly in older people, in which it decreases morbidity and mortality. 4,5 However, a body of literature data has demonstrated that long-term activities, having both elevated energy expenditure and high oxygen consumption, may promote ROS production and oxidative stress conditions, depending on duration and type of exercise, as well as on the individual's lifestyle and eating habits. 5,7 Human biochemical markers of oxidative stress are usually measured in plasma and in blood cells by several methods.…”
Section: Introductionmentioning
confidence: 99%